Analyzing the Effectiveness of Emotional Appeals in Advertising: A Comparative Study of Different Age Groups - Asep Zulkifli Achmad; Handi Dipo Santosa; Sheila Kurnia Putri (Jurnal Office, 2021)
Emotional appeals have been widely used in advertising to influence consumer behavior. However, the effectiveness of emotional appeals can vary depending on the age group of the target audience. Understanding how emotional appeals work among different age groups is essential for marketers to design more effective advertising strategies. The objective of this study is to analyze the effectiveness of emotional appeals in advertising among different age groups in Indonesia. This study employed a comparative research design, using a sample of 400 respondents from three age groups (young adults, middle-aged adults, and elderly adults). A survey questionnaire was used to collect data on respondents' emotional responses to different types of emotional appeals used in advertising. The results of this study showed that emotional appeals are more effective among young adults compared to middle-aged and elderly adults. Moreover, the study found that different types of emotional appeals (e.g., fear, humor, and nostalgia) have varying degrees of effectiveness among different age groups.